Zmiany dochodowe gospodarstw rolniczych w regionach Polski na podstawie wyników FADN - Czyżewski, Andrzej; Henisz-Matuszczak, Anna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The main goal of the study was an analysis of farm incomes in Poland according to regions, what let us come to conclusions about economic differentiation of agricultural farms, based on FADN's results for 2004 and 2005. The analysis was carried out in accordance with regions ("vertical") and through the prism of the production's and income's indexes ("horizontal") under criteria of economic size (ESU) and type of specialization. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1192, s. 186-194